Review of the Impact of Whale Fall on Biodiversity in Deep-Sea Ecosystems - Li, Qihui; Liu, Yaping; Li, Guo; Wang, Zhikai; Zheng, Zheng; Sun, Yuyang; Lei, Ningfei; Li, Qi; Zhang, Weizhen (Frontiers in Ecology and Evolution, 2022)
"Whale Fall" is a collective term for the marine ecosystem formed by the remains of whales that have died and entered the seafloor. The whale fall process produces a lot of unstable organic matter that has a significant impact on deep-sea ecosystems. Scientists speculate that organic matter input is the source of energy and material for organisms in deep-sea ecosystems. Due to the specificity of the time and space of the formation of whale fall, there are few studies on whale fall and its impact on the deep-sea ecosystem. This paper summarizes and analyzes the current research status on the distribution of whale fall and its impact on the deep-sea ecosystem at home and abroad. The results show that the current distribution of whale fall is mainly concentrated in the Pacific and Atlantic regions, and the research on the impact of whale fall on deep-sea ecosystems focuses on the formation process, degradation rate and impact on deep-sea biological systems. The research on the impact of whale fall on deep-sea ecosystems focuses on the formation process, degradation rate and the impact on deep-sea biological systems. This paper has some significance to the understanding of biodiversity and ecosystem succession in the deep-sea "desert area".